Design Of Web Based Employees Information System Design in SD Kumnamu School Tangerang - Rahayu, Sri; Muhtadi, Yudi; Al Farobie, Abizal (Pandawan, 2017)
ayroll systems in every company vary, most have used computer-based information systems, but there are still some companies that have not implemented it as in SD KUMNAMU SCHOOL. In this educational institution in the payroll information system is still using the calculation manually and using MS aids program. Excel. In this study using SWOT method as a method used to determine the strengths, weaknesses, opportunities, and system threats that run today through several stages of interview and literature study. Which produces a payroll information system that can manage computerized payroll, perform absentee calculations, automatically calculate monthly salary, allowances calculation, present salary slips and salary reports required every month or every year and others. System design using UML (Unified Modeling Language) tool, while in making system program using MySQL tool to design database and PHP (Hypertext Preprocessor) as programming language.